Analisis Nilai Karakter Disiplin Dalam Pembelajaran Kelas V SDN Wonorejo 1 Surabaya - Yossy Pitaloka; Aditya Dyah Puspitasari (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this research is to determine the Pancasila Student Profile, the sub-element of self-discipline in learning for class V students. This research uses descriptive qualitative research methods. The subjects used were class V students. The sampling in this study used purposive sampling. The research sample was 6 students, considering students with high cognitive scores, medium cognitive scores and low cognitive scores. Data collection uses observation sheets, interviews and documentation. The research results show: NF, IR, AY, ZD, RI, and ZL can enter on time respectively. The neatness, completeness and correctness of the uniforms used by NF, IR, AY, ZD, RI and ZL are good, complete and correct according to the respective schedule. NF, IR, AY, and ZD collected assignments on time twice, while RI and ZL respectively did not submit assignments on time. NF, IR, and AY did the task individually, while ZD did it twice and RI and ZL did not do it alone. No walking around while learning NF, IR, AY, ZD, RI, and ZL focus on their respective seats. Get motivation from teachers NF, IR, AY, ZD, RI, and ZL 3 days in a row. Get reward/punishment NF, IR, AY and ZD 1 time, while RI and ZL punishment 2 times.